Kekuatan Jaringan dan Modalitas Politik Kekerabatan Pilar Saga dalam Pilkada Tangerang Selatan 2020 - Hendy Setiawan; Khalimatus Sa’diyah (Bestuurskunde: Journal of Governmental Studies, 2021)
The issue of kinship politics networks and modalities Pilar Saga is built on the Ratu Atut Chosiyah's dynastic politics. Interestingly, the dynastic political network in Banten contributed to Pilar Saga's victory. Even the various corruption cases that ensnared Ratu Atut's family could not undermine her political network. For example, the corruption case of Ratu Atut for alleged bribery of the Constitutional Court and the trading of positions, T Chaeri Wardana for the corruption case of medical equipment, and Ratu Lilis Karyawati for the Cibenuangen River bypass case in Lebak, Banten. The purpose of this study was to analyze the extent to which Pilar Saga's kinship politics network and modalities influenced his victory in the 2020 South Tangerang Regional Head Election. This study used a qualitative approach with a descriptive method in South Tangerang. The research data was taken through observation and library research to strengthen the conclusion. The results show that the Pilar Saga political network and modalities, apart from being built from the Atut dynasty, were also boosted by the performance achievements of the incumbent Pilar Saga pair. The incumbent in the previous period with Airin Rachmi Diany (Atut's sister-in-law) was able to bring South Tangerang City to be the best Regency/City area in Banten in HDI (Human Development Index) numbers. On this basis, the rational behavior of voters in South Tangerang was not fooled by the various cases that ensnared their relatives in the corruption of the Ratu Atut Chosiyah dynasty.